A Emprical Investigation on Service Failure and Recovery at Retailing Bank in Vietnam - Binh, Tu Van; Vi, Nguyen Tran Phuong (UI Scholars Hub, 2021)
To identify factors affecting satisfaction with service recovery of banking sector and overall satisfaction, together with the effect of customersatisfaction on repurchase intent and word-of-mouth intent in the banking in Vietnam, a survey is conducted on 215 customers.Those respondents, who are buying services from the bank, namely Vietnamese Local Bank (VLB), have experienced in service failure and service recovery in their transaction with VLB, and lived in Ho Chi Minh City. Structural equation model (SEM) is employed to estimate the theoretical model and to test hypotheses. The findings of the study showed that distributive justice positively impact customer satisfaction with service recovery, and overall satisfaction. Satisfaction with recovery has a strong impact on overall satisfaction. Both satisfaction with recovery and overall satisfaction disclose a positive influence on repurchase intent, and only satisfaction with recovery positively affecting word-of-mouth intent.